Central Java Teachers’ Perspective on Science, Technology, Engineering and Mathematics (STEM) Learning - Astuti, Fiki Kusuma; Ellianawati, Ellianawati; Masturi, Masturi; Wiyanto, Wiyanto; Sumarni, Woro (Universitas Negeri Semarang, 2023)
The purpose of this study is to investigate central java teachers’ perspective about STEM. Science, technology, engineering and mathematics or STEM recently has been becoming the most discussed in education practice. Integrating engineering and technology with science and mathematics will help teachers to deliver material using real world problem. Using project based learning to solve the problem can enhance students’ interest, collaboration, discipline, critical and creative thinking skills. In fact, survey research showed that 35 of 72 teachers in central java do not know about STEM and teachers that have implemented STEM in the class have difficulties while teaching it. The highest hurdles teachers met was time allocation. Indonesian curriculum has a lot of materials that should have delivered in a limited time makes teachers hard to implement STEM in the learning process. Followed by teachers’ difficulties to integrate between science, technology, engineering and math because there is no curriculum materials to guide them and other difficulties are school infrastructure, students motivation, and lack of preparation. Time allocation, school infrastructures, STEM integration, and preparation are the most hurdles that teacher met in the class.